1995
DOI: 10.1093/clinids/21.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Necrotizing Fasciitis: Clinical Manifestations and Management

Abstract: Forty-five cases of cervical necrotizing fasciitis are reported, and their clinical, bacteriologic, and therapeutic implications are considered. Fasciitis was of dental origin in 78% of cases, pharyngeal in 16%, and surgical or posttraumatic in 6%. The condition extended to the face in 22% of cases, to the lower part of the neck in 56%, and to the mediastinum in 40%. Soft-tissue cultures were positive in 78% of cases. Anaerobes were isolated along with aerobes in 49% of cases (mean, 2.2 isolates per patient) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 32 publications
5
87
0
7
Order By: Relevance
“…Necrotizing fasciitis of the head and neck usually results from polymorphic flora including numerous bacilli and cocci and occurs around the scalp and facial areas or primarily in the neck. In a series of 45 cases, 3 anaerobes were isolated in 32 cases (71%). Anaerobes only were isolated in 10 cases (22%), while a mixture of anaerobic and aerobic organisms were found in 22 cases (49%).…”
Section: Discussionmentioning
confidence: 98%
“…Necrotizing fasciitis of the head and neck usually results from polymorphic flora including numerous bacilli and cocci and occurs around the scalp and facial areas or primarily in the neck. In a series of 45 cases, 3 anaerobes were isolated in 32 cases (71%). Anaerobes only were isolated in 10 cases (22%), while a mixture of anaerobic and aerobic organisms were found in 22 cases (49%).…”
Section: Discussionmentioning
confidence: 98%
“…C'est le seul examen accessible par le pouvoir d'achat des patients dans notre établissement et nos diagnostics reposaient sur la radiographie du thorax dans 85,71% des cas. Les littératures sont controversées, certains auteurs rapportent que cet examen n'est pas très utile dans l'évaluation ou le diagnostic de la médiastinite car ne montre que des signes tardifs (Mathieu, 1995). D'autres auteurs rapportent qu'il peut objectiver un élargissement du médiastin supérieur dans 40% des cas, un épanchement pleural uni ou bilatéral aspécifique dans 40% des cas, un emphysème sous cutané et/ou médiastinal dans 30% des cas, un niveau hydro-aérique médiastinal et épanchement péricardique dans 10% des cas (Doddoli, 2009).…”
Section: Discussionunclassified
“…To the best of our knowledge, this is the first report of monomicrobial cervicofacial necrotizing fasciitis due to H. influenzae. In a retrospective study of 45 patients with cervicofacial necrotizing fasciitis, H. influenzae was isolated from operative cultures in one case, although it is unclear whether other organisms were grown concomitantly (Mathieu et al, 1995). Almost half of the cases included in the study reported a predisposing condition including diabetes, alcoholism and malignancy.…”
Section: Discussionmentioning
confidence: 99%